(untitled) (Clinics, 2010)
OBJECTIVE: To describe the normal and variant anatomy of the coronary artery ostia in Indian subjects. INTRODUCTION: Anomalous coronary origins may cause potentially dangerous symptoms, and even sudden death during strenuous activity. A cadaveric study in an unsuspected population provides a basis for understanding the normal variants, which may facilitate determination of the prevalence of anomalies and evaluation of the value of screening for such anomalies. METHODS: One hundred and five heart specimens were dissected. The number of ostia and their positions within the respective sinuses were observed. Vertical and circumferential deviations of the ostia were observed. The heights of the cusps and the ostia from the bottom of the sinus were measured. RESULTS: No openings were present in the pulmonary artery or the non-coronary sinus. The number of openings in the aortic sinuses varied from 2-5 in the present series; multiple ostia were mostly seen in the anterior sinus. The majority of the ostia lay below the sinutubular ridge (89%) and at or above the level of the upper margin of the cusps (84%). Left ostial openings were mainly centrally located (80%), whereas the right coronary ostia were often shifted towards the right posterior aortic sinus (59%). DISCUSSION: The preferential location of the ostia was within the sinus and above the cusps, but below the sinutubular ridge. On occasion, normal variants like multiple ostia, vertical or circumferential shift in the position, and slit-like ostia may create confusion in interpreting the images and pose a difficulty during procedures like angiography, angioplasty, and coronary artery bypass grafting.